Sosialisasi Teknologi Pakan Amoniasi di Kelompok Tani Ternak Ambacang Permai Kabupaten Lima Puluh Kota - Yesi Chwenta Sari; Syafri Nanda; Fatma Poni Mardiah; Roza Yunita; Montesqrit Montesqrit (Warta Pengabdian Andalas, 2023)
The main feed for ruminants is forage, and its supply fluctuates greatly depending on the season. During the rainy season, the forage will thrive and be abundant, but the opposite condition, i.e. dry season, where farmers will have difficulty getting fresh forage. Meanwhile, animal feed must be continuously available. The solution is to use agricultural waste as an animal feed with limiting factors, namely high lignin content, low digestibility, low protein content, and anti-nutrients. Therefore, a feed processing technology known as Ammoniation is needed. Ammoniation is a chemical treatment of agricultural and plantation waste feed ingredients by adding chemicals like NaOH, KOH, or Urea. Ammoniation can reduce lignin and silica and increase protein content. Socializing ammoniation technology in the Ambacang Permai livestock farmer group, Lima Puluh Kota District, was necessary. The method included lectures, demonstrations of making rice straw ammoniation, discussions, and consultations on animal feed. This activity was expected to help group members to overcome the problem of providing ruminants' feed from crop residues and plantation waste, so it was expected to reduce feed costs and increase group business.